“The Effect Of Achievement Goals On Homework Behavior And Academic Emotions On Students Of Smp Negeri 1 Larantuka In East Flores Timur-Ntt-Indonesia” - TORON, VINSENSIUS BAWA; BHOKI, HERMANIA; KEBAN, YOSEP BELEN; BEDING, SKOLASTIKA LELU (Advances in Social Sciences Research Journal, 2021)
Research reveals the impact of achievement goals on behavior in doing assignments and academic emotions to achieve learning goals. The study was conducted on 1200 students at SMP 1 Larantuka with the conclusion that the Achievement Goal (X) has a positive and significant effect on the behavior of doing assignments (Y) as evidenced by an error rate of 0.05 (α = 5%), the path coefficient is 0.237, the Sig value is t is 0.000 (0.000 < 0.05) and the adjusted R Square y value is 0.053. Achievement Goal (X) has a positive and significant effect on academic emotion (Z) as evidenced by the error rate of 0.05 (α=5%), the path coefficient of 0.379, the Sig.t value of 0.000 (0.000 <0.05) and the value of Adjusted R Square of 0.141. Academic Emotion (Z) has a positive and significant effect on the behavior of doing tasks (Y) as evidenced by the error rate of 0.05 (α=5%), the path coefficient of 0.395, the Sig.t value of 0.000 (0.000 <0.05) and Adjusted R Square value of 0.153. The achievement goal (X) has no significant effect on the behavior of doing the task (Y) as evidenced by a significance value of 0.076>0.05 (α=5%). Academic Emotion (Z) has a positive and significant effect on the behavior of doing the task (Y) as evidenced by the error rate of 0.05 (α=5%), the path coefficient of 0.356, the Sig.t value of 0.000 (0.000 <0.05), R Square value is 0.165 and R Square value is 0.242